Faktor-faktor penentu dalam sejarah transformasi perwujudan Bangunan tinggal Bali aga - Ida Ayu Dyah Maharani; Imam Santosa; Prabu Wardono; Widjaja Martokusumo (Jurnal Kajian Bali (Journal of Bali Studies), 2017)
Bali Aga residential buildings which have a vernacular character believed to be built deliberately by humans as a shelter when they started to live settled in 8th to 13th century. The shape of Bali Aga residential buildings have a transformation in similarity and difference among Bali Aga villages, occur in each period of Bali Aga era in diachronic ways. This research traces the factors which influence that phenomenon. The Bali Aga era that rebranding attempted to an ancient, the new and the newest Bali Aga, show that transformation in the similarity and difference is not due to cultural overlapping only. The change of local environmental conditions and potential also affect it, in accordance with the vernacular concept. Both become the most important factors affecting the shape of Bali Aga residential buildings, which written in qualitative historiography method limited to the discussion about interior and façade of buildings.